(untitled) (Revista LIDER, 2018)
This article shows ethnographic findings on accordion assembly in the archipelago through the labor migration of chilotes in Patagonian territories of Chile and Argentina. Our hypothesis suggests thinking of trajectories related to the circulation of the instrument from Europe to Brazil in the middle of the nineteenth century.